Voluntary intake of Tanzania grass (Panicum maximum) under rotational grazing by lactating cows - Lima, MLP; Berchielli, T. T.; Nogueira, J.; Salman, AKD; Ruggeeri, A. C.; Leme, P. R.; Aroeira, LJM; Soares, JPG (Fundação Estudos Agrarios Luiz Queiroz (fealq), 2001)
The study was conducted at Nucleo de Pesquisas Zootecnicas Nordeste of the Instituto de Zootecnia, Ribeirao Preto, SP, in a rotational grazing area of Tanzania grass (Panicum maximum), to estimate the dry matter intake by lactanting cows. The estimation of dry matter intake was calculated from the feces production estimated using extrusa Chromium-mordent and the in vitro digestibility of diet. The three treatments were crossbreed cows fed 3 kg.day(-1) of concentrate, crossbred cows without concentrate suplementation and pure Gir cows also without concentrate supplementation. The milk production was 11.98, 6.53 and 5.46 kg per cow per day, the grass intake was 8.26 +/- 5.66, 11.01 +/- 5.37 and 9.55 +/- 2.31 kg of dry matter per day or 2.15%, 2.37% and 2.34% of live weight for the three experimental groups respectively. The milk production was higher (P<0.01) for cows fed with concentrate. No difference was found for dry matter intake.
Keywords: dry matter intake; Digestibility; marker indigested